Flow chart of the PSO optimized the Neural Network algorithm. - Ming Li (91180) (2025)
The dashed rectangular frame portion on the left is the PSO algorithm. The PSO algorithm provide initial weights and thresholds of the Neural Network. The dashed rectangular frame portion on the right is the Neural Network algorithm.